We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
134
1
avatar

Let f(x) = log_b x, and let g(x) = x^2 - 4x + 4. given that f(g(x)) = g(f(x)) = 0 has exactly one solution and that b > 1, compute b.

 Jul 19, 2019
 #1
avatar+105484 
+2

f(x)  = logb x     g(x)  = x^2 -4x + 4        f(g)  = 0   and g(f)  = 0

 

So

f(g)  = logb [ x^2 -4x + 4]   = 0

So....in exponential form

b^0  = x^2 -4x +4

1 = x^2 -4x + 4

x^2 - 4x +3  = 0

(x -3) ( x -1)  =0

x  =  3  or   x =1

 

And

g(f)  =     [ logb x]^2 - 4[logb x ]  + 4   =   0        [remember  that   log b 1  =  0 ]....so.....

If x  = 1  ⇒  [log b 1 ]^2   - 4[ log b 1]  + 4   ⇒  [0]^2 - 4 [0 ] + 4  = 4

So....x  =1 doesn't lead to a solution

 

If x  = 3

[ log b 3 ]^2  - 4 [log b 3 ]  +  4   =  0    ....... and by a log property

2logb 3   - 4 log b 3  +  4  = 0

-2logb 3  + 4   = 0

4  = 2 log b 3

2 = log b 3

 

In exponential form

b^2  = 3       and since b > 1

b = √3

 

cool cool cool

 Jul 19, 2019

25 Online Users

avatar
avatar
avatar